2022
DOI: 10.1002/admi.202101589
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity Enabled by Load‐Driven Redistribution of Electrons

Abstract: How to reduce friction is a key issue of tribology and plays an important role in solving a number of problems of physics and engineering, e.g., the durability of the nano-friction generator. [2] The well-known and widely used Amontons-Coulomb friction law stipulates that the tangential frictional force is proportional to the normal compressive force. [3] With the main advantage of being simple, this phenomenological macroscopic law fails to be applicable in the field of nano-tribology. [4] Indeed, nano-frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…5,6 In recent decades, the realm of exploring superlubricity in both solids and liquids has garnered significant interest in the fields of fundamental science and engineering, thus, witnessing significant strides. For solid lubrication materials, such as MoS 2 , 7 graphene, 8 hexagonal boron nitride, 9 and diamond-like amorphous carbon coatings, 10 the realization of superlubrication required some strict conditions such as the incommensurate contact state, the protection of inert gases, or an ultrahigh vacuum condition, which limited its application. 11−13 To date, liquid superlubrication systems can be divided into water-and acid-based solutions, hydrated materials, ionic liquids, 2D materials as lubricant additives, and oil-based lubrication materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 In recent decades, the realm of exploring superlubricity in both solids and liquids has garnered significant interest in the fields of fundamental science and engineering, thus, witnessing significant strides. For solid lubrication materials, such as MoS 2 , 7 graphene, 8 hexagonal boron nitride, 9 and diamond-like amorphous carbon coatings, 10 the realization of superlubrication required some strict conditions such as the incommensurate contact state, the protection of inert gases, or an ultrahigh vacuum condition, which limited its application. 11−13 To date, liquid superlubrication systems can be divided into water-and acid-based solutions, hydrated materials, ionic liquids, 2D materials as lubricant additives, and oil-based lubrication materials.…”
Section: Introductionmentioning
confidence: 99%
“…Since it can decrease resistance and save energy, materials with superlubricity are of tremendous importance from the perspective of saving energy and protecting the environment. , In recent decades, the realm of exploring superlubricity in both solids and liquids has garnered significant interest in the fields of fundamental science and engineering, thus, witnessing significant strides. For solid lubrication materials, such as MoS 2 , graphene, hexagonal boron nitride, and diamond-like amorphous carbon coatings, the realization of superlubrication required some strict conditions such as the incommensurate contact state, the protection of inert gases, or an ultrahigh vacuum condition, which limited its application. …”
Section: Introductionmentioning
confidence: 99%
“…Friction and wear are two main modes of energy dissipation and component failure in various mechanical systems, [ 1 ] especially in micro‐nano devices under strong confinement and extreme external conditions where liquid lubricants fail. [ 2 ] Superlubricity, [ 3,4 ] a slipping state with ultra‐low friction, which is desirable for various applications that involve the sliding contact between two components, [ 5 ] is thus paramount to tribology and surface science. To achieve superlubricity for two solids in sliding contact, the ratio between the lateral and normal stiffnesses [ 6,7 ] is optimized, an external field actuation is applied, [ 8 ] or the contact is rendered and kept incommensurate, [ 9 ] so as to eliminate the potential barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the electric-field-controlled charge depletion or accumulation of semiconductor and metallic materials would fundamentally lead to the change in charge density distribution across the device surface. Recent researches have revealed a strong correlation between charge redistribution and interfacial adhesion and friction. Cheng et al and Song et al have proposed quantitative models that describe the impact of load/electric-field-induced charge redistribution and current-induced electron transfer on the sliding barrier, respectively. Sun et al have utilized density functional theory (DFT) calculations to establish a universal connection between sliding energy landscapes and the evolution of charge redistribution along sliding pathways.…”
mentioning
confidence: 99%
“…To uncover the physical mechanism underlying the relationship between electric properties and friction, we further calculated the charge density redistribution ( ρ diff ( x , y , z )) between Si(111) and graphene/ h -BN during sliding. Given that friction essentially arises from electromagnetic interaction, and charge density redistribution is closely associated with interfacial friction. , It is observed that the ρ diff ( x , y , z ) between Si(111) and graphene/ h -BN changes significantly upon applied electric field, companying with the transfer of charge from the graphene into Si(111) layer (Figure S8a). To quantify this effect of electric field on the charge density distribution, the evolution of the charge density redistribution (Δ ρ diff ) was assessed using the method proposed by Sun et al (see Section 10 of the SI for details), who has reported a linear relationship (Δ E = k Δ ρ diff ) between Δ ρ diff and Δ E on the van der Waals (vdW) joints (e.g., MoS 2 /MoS 2 , graphene/graphene), metallic joint (Cu/Cu), ionic joint (NaCl/NaCl), and covalent joint systems without external electric field.…”
mentioning
confidence: 99%